2011
DOI: 10.3168/jds.2010-3962
|View full text |Cite
|
Sign up to set email alerts
|

Invited review: Are adaptations present to support dairy cattle productivity in warm climates?

Abstract: Environmental heat stress, present during warm seasons and warm episodes, severely impairs dairy cattle performance, particularly in warmer climates. It is widely viewed that warm climate breeds (Zebu and Sanga cattle) are adapted to the climate in which they evolved. Such adaptations might be exploited for increasing cattle productivity in warm climates and decrease the effect of warm periods in cooler climates. The literature was reviewed for presence of such adaptations. Evidence is clear for resistance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0
15

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(124 citation statements)
references
References 88 publications
3
106
0
15
Order By: Relevance
“…In order to decrease heat load cows seek shade. Reduced heat production is usually achieved with decreased feed intake, less physical activity as walking or ruminating and lowered milk production (Silanikove, 2000;Berman, 2011;Renaudeau et al, 2012). The choice of which strategy to be used may change depending on weather conditions and on the cow's own characteristics, such as size, body surface, hair coat length and color, as well as metabolic rate (McManus et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In order to decrease heat load cows seek shade. Reduced heat production is usually achieved with decreased feed intake, less physical activity as walking or ruminating and lowered milk production (Silanikove, 2000;Berman, 2011;Renaudeau et al, 2012). The choice of which strategy to be used may change depending on weather conditions and on the cow's own characteristics, such as size, body surface, hair coat length and color, as well as metabolic rate (McManus et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Indolicidin, the protein product of CATHL4, can induce autophagic cell death in the parasite Leishmana donovani, the causative agent of the parasitic disease Leishmaniasis (Bera et al 2003). This is particularly interesting as the indicine breeds are known for their increased parasite resistance compared to taurine breeds (Berman 2011). Knockouts of CATH-family genes in mice have revealed that the antimicrobial peptide products of Cold Spring Harbor Laboratory Press on May 7, 2018 -Published by genome.cshlp.org Downloaded from these genes influence Leishmaniasis lesion development and tissue colonization of the parasite (Kulkarni et al 2011).…”
Section: Copy Number Polymorphic Genesmentioning
confidence: 99%
“…While both taurine and indicine individuals had CNVs that intersected immune function-related genes, the distinct resistance traits of zebu cattle (Berman 2011) lend great importance to the study of Bos taurus indicus-specific immune function gene CNVs. In that regard, we have identified several CNVs that may represent variations between BINE and the remaining B. t. taurus animals.…”
Section: Heatmap Analysesmentioning
confidence: 99%
“…These abilities are referred as adaptability. They mainly rely on functional traits such as reproductive, metabolic, neurological, immunological traits and hair coat characteristics (Berman, 2011). In this study, we determined the adaptive traits perceived by local stakeholders which can be equally relevant to give perspectives on the use of these local breeds in the future.…”
Section: Discussionmentioning
confidence: 99%